Parental bereavement and the loss of purpose in life as a function of interdependent self-construal - Kim, Jinhyung; Hicks, Joshua A. (Frontiers in Psychology, 2015)
Children are often inextricably linked to their parents’ hopes and dreams. As such, the loss of a child often represents one of the most traumatic experiences possible. The current research explores how this specific loss relates to one’s sense of purpose in life. We further explore whether the loss of a child is particularly detrimental to one’s sense of purpose for highly interdependent parents. Analyses of parents from the Midlife in the United States data set revealed, as expected, that the loss of child negatively predicts one’s sense of purpose in life, and that this effect is most pronounced for parents high in interdependent self-construal. Potential mechanisms and implications of the present findings are discussed.